Analisis Yuridis Kekuatan Pembuktian Sertipikat Hak Milik sebagai Bukti Terkuat Dibandingkan dengan Bukti Hak Lainnya dalam Undang-Undang Pokok Agraria (Studi Putusan Mahkamah Agung Nomor 2064 K/Pdt/2014) - Muhammad Satria Harry Dhan (Jurnal Perspektif Hukum, 2021)
In agrarian, land is a part of the earth called earth surface. Regulations on land in this case do not necessarily refer to the regulations concerning all of its aspects, but only refers the regulatios on one of it aspects i.e. land in juridical definition named rights that produce two principles. The principles create 2 land registration system; namelt positive and negative publication system. A dispute over overlapping land ownership is found at Kelurahan Sukaraja, Medan Maimun Sub-district, Medan, North Sumatera Province. This case begins with lawsuit filed by the plaintiff. The object of this case is a piece of land with area of 1.080 m2 that is partly owned by Datuk Syahrial, but it has been seized and occupied by Lido Hamonangan Hutabarat without any permission from Datuk Syahrial. The land was acquired by the plaintiff from his parents grounded on a letter of notification, then Datuk Muhammad Tamin bin Datuk Rashtam acquired the land from his parents named Datuk Rashtam. However, the land and building on it are registered with the name of Lido Hamonangan Hutabarat who acquired it from plaintiff I grounded on a sale and purhace deed drawn up before a Notary, Roesli, in Medan. This case was submitted the favor of the plaintiff. This research employs Normative Juridical method and applies the theories of legal certainly and rights. The legal consequences for the verification strength of the land ownership certificate in this case is that the grant process seems ti be vague, whether it truly happened and whether it was actually handed by Datuk Mhd.Tamin or not. There is not any authentic evidence showing that there was actually a real grant (Grant Letter) from Datuk Mhd. Tamin to Datu Kamal. The analysis of the Supreme Court Verdict Number 2064K/Pdt/2014 is that the Land Act (the Laws on Basic Regulations on Agrarian Principles) regulates that it is necessary to look into the process of receiving the grant, whether or not the transfer of the land ownership right or the grand has been in line with Chapter IV Article 210 of the Islamic Law Compilation.